Social challenges and opportunities in agroforestry: cocoa farmers’ perspectives - Bosselmann, A.S.; Boadi, S.A.; Olwig, M.F.; Asare, R. (Palgrave Macmillan, 2024)
Agroforestry practices in cocoa cultivation have historical roots going back to the Mayan sacred groves in Mesoamerica. Today, agroforestry cocoa, i.e., the integration of shade trees, plants and crops in cocoa systems, is promoted as a climate smart practice by public and private institutions. Shaded cocoa can sustain or even increase cocoa yields and the agroforestry systems may provide additional output for household consumption and sale as well as improve the microclimate and soil conditions on the farm. Despite these promising features, cocoa agroforestry systems are far from the norm in producing countries like Ghana. Based on discussions with groups of farmers across the Ghanaian cocoa belt, this chapter shows that while farmers are well aware of the positive aspects of shaded cocoa systems, traditional cocoa practices, village chiefs’ command of local land uses, land and tree tenure systems, alternative land uses and inability to access inputs and extension services limit the adoption and constrain the management of shade trees. As still more policies are developed to improve the Ghanaian cocoa sector, policymakers must consider these often overlooked social and institutional factors that prevent cocoa farmers from engaging in longer-term agroforestry practices and thereby benefiting from the opportunities they present.